Do People Avoid Morally Relevant Information? Evidence from the Refugee Crisis - Freddi, Eleonora (The Review of Economics and Statistics, 2021)
Abstract Combining click data from a swedish newspaper and administrative data on asylum seekers in sweden, i examine whether a larger presence of refugees in a municipality induces people to avoid news that may encourage welcoming the newcomers. Exploiting the unexpected inflow of refugees to Sweden during 2015 and their exogenous allocation across Swedish municipalities, I find that people living in municipalities where the relative number of refugees is larger read fewer articles about asylum seekers. The decrease in clicks is 36% larger for more empathic articles and is correlated with less engagement in activities aimed at welcoming refugees.